2021
DOI: 10.48550/arxiv.2106.14961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The completed SDSS-IV extended Baryon Oscillation Spectroscopic Survey: measurement of the growth rate of structure from the small-scale clustering of the luminous red galaxy sample

Abstract: We measure the small-scale clustering of the Data Release 16 extended Baryon Oscillation Spectroscopic Survey Luminous Red Galaxy sample, corrected for fibre-collisions using Pairwise Inverse Probability weights, which give unbiased clustering measurements on all scales. We fit to the monopole and quadrupole moments and to the projected correlation function over the separation range 7 โˆ’ 60 โ„Ž โˆ’1 Mpc with a model based on the cosmological emulator to measure the growth rate of cosmic structure, parameterized by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 64 publications
4
21
0
Order By: Relevance
“…The positions of the BOSS galaxies are converted from RA, DEC and redshift to Cartesian coordinates assuming a Planck 2016 ฮ›CDM model with โ„ฆ m = 0.307. The choice of cosmology for this transformation has a negligible impact on the final result (Chapman et al 2021;Lange et al 2021).…”
Section: Measurement From Bossmentioning
confidence: 99%
See 1 more Smart Citation
“…The positions of the BOSS galaxies are converted from RA, DEC and redshift to Cartesian coordinates assuming a Planck 2016 ฮ›CDM model with โ„ฆ m = 0.307. The choice of cosmology for this transformation has a negligible impact on the final result (Chapman et al 2021;Lange et al 2021).…”
Section: Measurement From Bossmentioning
confidence: 99%
“…Based on the Aemulus suite, Lange et al (2021) measured the linear growth rate for the BOSS-LOWZ galaxies using clustering measurement on small scales, while Chapman et al (2021) applied the emulator method of Zhai et al (2019) and performed a cosmological analysis with eBOSS LRG data using a similar range of scales. This work extends the previous works in three different ways.…”
mentioning
confidence: 99%
“…Comparable gains in cosmological constraining power from the nonlinear regime of BOSS LOWZ galaxies were also found in Wibking et al (2020). In closely related work analyzing the clustering of the Luminous Red Galaxy sample in eBOSS (Chapman et al 2021), it was found that constraints on f ฯƒ 8 are improved by 70% when including information from nonlinear scales.…”
Section: Introductionmentioning
confidence: 75%
“…40 of these simulations form a training set that has already been used to successfully train an emulator for the correlation function in redshift space (Zhai et al 2019). This emulator has recently been used to measure the growth rate from the eBOSS LRG sample (Chapman et al 2021). These 40 simulations sample a seven dimensional cosmological parameter space, with parameters {ฮฉ ๐‘š , ฮฉ ๐‘ , ๐œŽ 8 , โ„Ž, ๐‘› ๐‘  , ๐‘ eff , ๐‘ค 0 }.…”
Section: Parameter Space and Training Datamentioning
confidence: 99%